From social representations to action: proximity and the relation between social representations of the development of intelligence and authoritative parenting style / De las representaciones sociales a la acción: proximidad y relación entre las representaciones sociales del desarrollo de la inteligencia y un estilo parental democrático. Issue 2 (3rd May 2016) - Miguel, Isabel; Valentim, Joaquim P.; Carugati, Felice
Abstract: A well-established body of literature holds that the construction of social representations of intelligence is guided by the subjective inexplicability about the target-topic and by the social identities of subjects. Within the general framework of the sociogenesis of social representations, this article aims to explore the role of social positions in organizing an individual's reported action towards the object of representation. A theoretical model which examines the relations between social representations of the development of intelligence, parental goals and the authoritative parenting style was tested in sub-samples of educators, which included 227 mothers, 117 fathers and 122 mother-teachers. Structural equation modeling procedures indicated, as hypothesized, that specific socio-cognitive dynamics are relevant in shaping the patterns of relations with the object of representation, suggesting that these dynamics are a result of the organization of multiple discourses where content, social positions and behavioural interaction are strongly intertwined. Theoretical contributions of findings are discussed.